2023
DOI: 10.3389/fpubh.2023.1193789
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of active aging and quality of life among older adults: systematic review

Abstract: IntroductionPopulation demography across the globe shows an increasing trend in the aging population due to better healthcare, improved nutrition, advanced health-related technology, and decreased fertility rate. Despite these advancements, there remains a knowledge gap in understanding the association between active aging determinants and quality of life (QoL) among older adults, particularly within diverse cultural contexts, which has not been adequately explored in previous research. Therefore, understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Overall, we found that both structured exercise for competition and unstructured physical activity have several advantages on the health-related parameters taken into account, in comparison to the sedentary population. In accordance with previous research, engaging in regular physical activities can improve physical abilities and mental health ( 13 , 62 ). Prior studies have proposed various exercise programs with both multi-dimensional and single-component approaches, with some showing greater benefits than others, but all demonstrating positive effects ( 29 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, we found that both structured exercise for competition and unstructured physical activity have several advantages on the health-related parameters taken into account, in comparison to the sedentary population. In accordance with previous research, engaging in regular physical activities can improve physical abilities and mental health ( 13 , 62 ). Prior studies have proposed various exercise programs with both multi-dimensional and single-component approaches, with some showing greater benefits than others, but all demonstrating positive effects ( 29 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, [56] opine that improving a sense of community by reducing social isolation and loneliness enhances health. [57] agree that the quality of living spaces is a quality health determinant. In health resorts, research links nature experience to psychological dimensions, perceptions and interactions with stimuli from the natural world through sensory modalities-sight, hearing, taste, touch, and smell [58].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Card (2017) defines the aging phase as beginning at 65 years old and beyond, categorizing this demographic into distinct groups: individuals aged 65-74 years are considered younger older adults, those aged 75-84 years are classified as advanced older adults, and those aged 85 and older are designated as very advanced older adults (Aslan et al, 2024). Aging is a complex process involving psychological, social, and physical dimensions, leading to various changes such as reduced cognitive abilities, decreased productivity, impaired attention, and weakened short-term memory (Marzo et al, 2023;Aktaş & Bakan, 2021). Foster & Walker, 2021;Sayın Kasar & Karadakovan, 2017).…”
Section: Introductionmentioning
confidence: 99%